Canada : Selected Issues and Analytical Notes. (IMF Staff Country Reports; Country Report ;, 2017)
This paper describes the proposed Canada Infrastructure Bank (CIB) that will be allocated Can USD 35 billion over an 11-year period. It will add to, and not replace, existing methods of financing public infrastructure at all levels of government, including the Federal Government's Can USD 187 billion Investing in Canada plan covering 12 years. The CIB will be a wholly government-owned Crown corporation, subject to provisions of the Financial Administration Act (FAA), including the requirement to prepare a corporate plan, operating budget, and capital budget, for approval by the Government. The CIB and its investments will be on the federal government's balance sheet. However, the infrastructure-related special purpose vehicles (SPVs) in which the CIB invests will not be on the government's balance sheet. Attracting private capital requires offering a rate of return acceptable to the investor. Worldwide, there are trillions of dollars looking for safe returns over the long-term. The risk-adjusted rate of return sufficient to attract an investor is not known with precision ex-ante. Investors will seek the highest rate of return possible above its minimum threshold.